2017
DOI: 10.1155/2017/6586157
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Birdshot Retinochoroiditis and Retinal Astrocytoma

Abstract: Background. This case highlights the importance of recognising multiple pathologies within the eye which may not necessarily be linked. Both birdshot retinochoroiditis and astrocytoma are rare conditions. The case underlines the need for early identification and treatment of birdshot retinochoroiditis with steroids and disease modifying drugs. Astrocytoma in the absence of tuberous sclerosis is also uncommon. Case Presentation. A 36-year-old male presented with 3-month history of bilateral progressive flashing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The defining feature of DR is irregularities in the retinal vasculature, which can develop into irreversible visual loss as a result of scarring or bleeding [1,5]. As a result, there could be a gradual loss of eyesight and, in the most extreme case, blindness.…”
Section: Main Textmentioning
confidence: 99%
“…The defining feature of DR is irregularities in the retinal vasculature, which can develop into irreversible visual loss as a result of scarring or bleeding [1,5]. As a result, there could be a gradual loss of eyesight and, in the most extreme case, blindness.…”
Section: Main Textmentioning
confidence: 99%
“…Retinal vasculature abnormalities are the hallmark of DR, which can progress to irreversible vision loss due to scarring or hemorrhage [ 1 , 5 ]. This may cause gradual vision impairment and, in its most severe form, blindness.…”
Section: Introductionmentioning
confidence: 99%
“…According to epidemiology studies conducted Diagnostics 2023, 13, 2645 2 of 21 in Europe, America, Asia, and Australia, there will be 154.9 million people with DR by 2030, up from 100.8 million in 2010, with 30% of them in danger of going blind [2]. DR accounts for 2.6% of blindness causes worldwide [3]. Despite the alarming statistics, research has revealed that more than 90% of new DR cases might be reduced with the right care, vigilance, and monitoring of the eyes.…”
Section: Introductionmentioning
confidence: 99%